Solar water disinfection by photocatalytic singlet oxygen production in heterogeneous medium - Villén, Laura; Manjón, Francisco; García-Fresnadillo, David; Orellana, Guillermo (Applied catalysis. B, Environmental, 2006)
Water disinfection in isolated rural areas of less-developed countries poses specific problems since operational expenses must be low, chemicals are not easily deployable and qualification of operators is scarce. Therefore, alternative technologies to the widespread chlorination have been considered for household use. We have evaluated the viability of a photocatalytic process for bacteria inactivation with sunlight, affordable 0.8m2 compound parabolic collectors (CPC) and an UV–vis absorbing ruthenium (II) tris–chelate complex immobilised (2gm−2) onto porous silicone as singlet molecular oxygen generator. We have tested the efficiency of two CPC prototypes with different configuration of the photosensitising material, namely, a coaxial- and a fin-type one. Mineral water flowing at 2Lmin−1 and spiked with Escherichia coli or Enterococcus faecalis was subject to the photocatalytic treatment for 5h (a 0.6–0.8MJm−2L−1 dose of 360–700nm sunlight radiation at 40°N latitude). Using the fin-type reactor under these conditions, the bacterial survival for 104 to 102CFUmL−1 initial concentrations drop to ca. 1% and 0.1% for E. coli and E. faecalis, respectively. The average disinfection rates are similar with both photoreactor designs, regardless the bacteria used (ca. 2×104 and 2×106CFUL−1h−1 for the low and the high initial levels of bacteria, respectively). The novel systems are comparable to or better than solid-supported TiO2 photocatalysts at inactivating waterborne bacteria.